Enhancement of machinability by workpiece preheating in end milling of Ti-6Al-4V - Hossain, Muhammad Ishtiyaq; Amin, A. K. M. Nurul; Patwari, Muhammed Anayet Ullah; Karim, A. (International OCSCO World Press, 2008)
Purpose: The main objective of this paper is to investigate the effect of workpiece preheating with high frequency induction heating on improvement of machinability of Ti-6Al-4V during end milling using PVD TiAlN coated inserts. Tool life, cutting force and vibration were investigated during the experiments. Design/methodology/approach: End milling tests were conducted on Vertical Machining Centre (VMC ZPS, Model: MCFV 1060 with quarter immersion cutting. Titanium based alloy Ti-6Al-4V bar was used as the work-piece. Machining was performed with a 20 mm diameter end-mill tool holder (R390-020B20-11M) fitted with one insert. PVD TiAlN coated carbide inserts (R390-11 T3 08E-ML 2030) were used in the experiments. All of the experiments were run at room temperature and preheated conditions. The preheated temperature was maintained at 420ºC and no phase change of the workpiece in preheating was ensured from the phase diagram of Ti-6Al-4V. High frequency induction heating was utilized to run the preheated machining. Findings: Preheating helps in substantially increasing tool life and in lowering down the cutting force value, lowering the amplitude of vibration and dynamic forces. Practical implications: The cost of machining Ti-6Al-4V is extremely high because of the relatively low machining speed and short tool life. Therefore, improving the machinability of Ti-6Al-4V is a research topic of much interest, with a number of approaches reported with varied results, such as, cryogenic cutting, highpressure coolant, rotary-tool, and minimum quantity lubrication (MQL). Originality/value: A new approach of induction preheating to overcome the difficulties in machining of Ti-6Al-4V is presented in this paper. In preheated machining, high frequency induction heating is used as an external heat source to soften the work material surface layer in order to decrease its tensile strength and strain hardening. An experimental study has been performed to assess the effect of workpiece preheating using induction heating system to enhance the machinability of Ti-6Al-4V. The preheating temperature was maintained below the phase change temperature of Ti-6Al-4V.